Article 13 TFEU and the protection of animals as sentient beings: a judgment of the Italian Court of Cassation (Criminal Division) - Germanò, Alberto (Przegląd Prawa Rolnego, 2021)
Animals, considered as “things” by Aristotle, “res mancipi” by the Romans and “goods” by the Italian Civil Code of 1942, are defined in Article 13 of the 2007 Treaty on the Functioning of the European Union as “sentient beings,” beings capable of feeling pleasure and pain. The case concerns a deer wounded by a gunshot, which, still alive and writhing, was placed on the load bed of a vehicle. The Italian Supreme Court found that by doing so the hunter committed an offence under Article 544 of the Penal Code and adjudicated a penalty on the hunter for failing to kill the animal by a final blow to put an end to its suffering and agony.